PENGARUH MOTIVASI DAN KOMITMEN ORGANISASIONAL TERHADAP KEPUASAN KERJA PADA PEGAWAI TATA USAHA (Studi pada Tujuh Fakultas di Universitas Negeri Jakarta) - Paramita, Widya; Larasati, Dianty; Handaru, Agung Wahyu (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2014)
The purpose of these research are: 1) To know the description of the motivation, organizational commitment, job satisfaction, and working period at the State University of Jakarta. 2) To know the influence of motivation which had been controlled by working period on job satisfaction at State University of Jakarta. 3) To know the influence of organizational commitment which had been controlled by working period on job satisfaction at State University of Jakarta. 4) To know the influence of motivation and organizational commitment which had been controlled by working period simultaneously influence on job satisfaction at State University of Jakarta. The analysis conducted in this research is descriptive and explanatory analysis. The study was conducted on civil servants at seven faculties in the State University of Jakarta, while the techniques of data collection was done by distributing questionnaires and the data being processed using SPSS. The regression shows that there is influence between motivation which had been controlled by working period towards job satisfaction and there is influence between organizational commitment which had been controlled by working period towards job satisfaction. Motivation and organizational commitment which had been controlled by working period simultaneously influence job satisfaction with significance value. Keywords: motivation, Organizational Commitment, Working period, Job Satisfaction